PENGARUH PENDAPATAN DAN BELANJA TERHADAP FINANCIAL SUSTAINABILITY PEMERINTAH PROVINSI DI INDONESIA - Marshella, Ida; Dewata, Evada; Indriasari, Desi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
Financial Sustainability (FS) fluctuates in each period in provincial governments in Indonesia in 2019-2022. This indicates that there are variations in the level of adequacy and stability of public services provided by the provincial government. It also shows variations in the level of adequacy and stability of public services felt by the community. This study aims to determine Revenue and Expenditure on Financial Sustainability in Provincial Governments in Indonesia for the 2019-2022 Period. The independent variable is Revenue and Expenditure and the dependent variable is Financial Sustainability. The population in this study was 34 Provincial Government financial reports over 4 years so a sample of 136 provincial government financial reports in Indonesia was obtained. This study uses multiple regression analysis methods using the Eviews-12 application. The type of research conducted is casually associative with Goal Setting theory. The results of this study state that Revenue and Expenditure affect Financial Sustainability in Provincial Regional Governments in Indonesia for the 2019-2022 Period. Province in Indonesia 2019-2022 Period. With an R2 value of 87.07%.